Is one hair lock really representative?. Issue 1 (June 2014) - Dussy, Franz; Carson, Nicholas; Hangartner, Sarah; Briellmann, Thomas; Agius, Ronald
<x xml:space="preserve">Abstract</x> When investigating someone's hair a single lock is cut, washed, extracted and analysed. The forensic institutes in Switzerland agreed to retain a second lock for a possible reassessment. We were interested in the reproducibility of the concentrations of analytes in hair locks taken from different areas of the head of the same person covering the same time period. Therefore we analysed ethyl glucuronide and caffeine as model substances in 10 hair locks from three individuals categorised as social drinkers. The individual coefficients of variation varied between 14% and 28% for ethyl glucuronide and between 13% and 62% for caffeine corresponding to factors of 1.6 to 4.2 for the highest to the lowest concentrations between the hair locks. This finding has a significant importance both when the second hair lock has to be analysed in a forensic case and if the interpretation of the result is depending on a cut‐off value. Copyright © 2014 John Wiley & Sons, Ltd.